SISTEM INFORMASI BERBASIS WEB UNTUK PENGELOLAAN ARENA OLAHRAGA PADA APRIDA SPORT CENTER JAKARTA - Andy Dharmalau; Yogasetya Suhanda; Johan Anda (Institut Teknologi dan Bisnis (ITB) Swadharma, 2022)
The competition between sports arena businesses today is very tight and few can survive. So it takes good management to survive. Apart from having complete availability and services, Aprida Sports Center does not yet have a good system in processing transaction data for its operational activities. So that there are often errors in booking data, payment transactions, and difficulties in making reports. This reason makes the writer interested in this research to evaluate the implementation of transaction data processing on the running system. The purpose of this research is to solve the problems that occur in the exiting conditions. The design of the sports arena management system uses PHP programming and MySql database to make it easier to apply. With the information system for managing the sports arena, customers, prospective customers, and owners can easily access the information about the field. The sports arena management information system is run as expected.